Elabela gene therapy promotes angiogenesis after myocardial infarction. Issue 17 (21st July 2021) - Jin, Liangli; Pan, Yang; Li, Quanyi; Li, Jing; Wang, Zhi
Abstract: This study was aimed at investigating whether Elabela (ELA) gene therapy can promote angiogenesis in the treatment of myocardial infarction (MI). The fusion expression plasmid pAAV‐3 × Flag/ELA‐32 was successfully constructed using molecular cloning technique. The model of acute MI was established by ligating the left anterior descending coronary artery in mice. Adeno‐associated virus serotype 9 (AAV9) was injected into the surrounding myocardium and tail vein immediately after the model was established. AAV was injected again from the tail vein one week later. Compared with the MI+PBS (control) group, the serum N‐terminal pro‐brain natriuretic peptide (NT‐proBNP) concentration, and the values of left ventricular end‐diastolic diameter (LVDd) and left ventricular end‐systolic diameter (LVDs) of the MI+AAV‐ELA (gene therapy) group were significantly decreased, while the value of left ventricular ejection fraction was significantly increased at 2 and 4 weeks after operation. Compared with the control group, the expression of CD105 and vWF and the percentage of CD31‐ and Ki67–co‐positive cells were significantly increased in the gene therapy group. Moreover, the expressions of apelin peptide jejunum (APJ) receptor, vascular endothelial growth factor (VEGF), VEGFR2, Jagged1 and Notch3 in the heart tissue around the infarction were up‐regulated in mice with gene therapy. The results suggest that ELA activates VEFG/VEGFR2 and Jagged1/Notch3 pathways through APJ to promote angiogenesis after myocardial infarction. ELA gene therapy may be used in the treatment of ischaemic cardiomyopathy in future.